T memory stem cell characteristics in autoimmune diseases and their promising therapeutic values - Fazeli, Pooria; Kalani, Mehdi; Hosseini, Maryam (Frontiers in Immunology, 2023)
Memory T cells are conventionally subdivided into T central memory (TCM) and T effector memory (TEM) cells. However, a new subset of memory T cells named T memory stem cell (TSCM) cells has been recognized that possesses capabilities of both TCM and TEM cells including lymphoid homing and performing effector roles through secretion of cytokines such as interleukin-2 (IL-2) and interferon-gamma (IFN-γ). The TSCM subset has some biological properties including stemness, antigen independency, high proliferative potential, signaling pathway and lipid metabolism. On the other hand, memory T cells are considered one of the principal culprits in the pathogenesis of autoimmune diseases. TSCM cells are responsible for developing long-term defensive immunity against different foreign antigens, alongside tumor-associated antigens, which mainly derive from self-antigens. Hence, antigen-specific TSCM cells can produce antitumor responses that are potentially able to trigger autoimmune activities. Therefore, we reviewed recent evidence on TSCM cell functions in autoimmune disorders including type 1 diabetes, systemic lupus erythematosus, rheumatoid arthritis, acquired aplastic anemia, immune thrombocytopenia, and autoimmune uveitis. We also introduced TSCM cell lineage as an innovative prognostic biomarker and a promising therapeutic target in autoimmune settings.